Hubungan Antara Kekuatan Otot Lengan Dan Koordinasi Mata Tangan Dengan Ketepatan Shooting Dalam Olahraga Petanque Di MBC (Masbagik Bocce Club) - Lalu Hulfian; Asrul Sani (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
This study aims to determine the relationship between arm muscle strength and hand-eye coordination on shooting accuracy in the petanque game at MBC (Masbagik Bocce Club) in 2020. The research design used in this research is descriptive quantitative with a correlational method. The collection technique uses descriptive correlation by collecting data from surveys, technical tests, and measurements. The results show the relationship between arm muscle strength and hand-eye coordination on shooting accuracy in the petanque game at MBC (Masbagik Bocce Club) 2020 is very significant, with a level of 0.05. In conclusion, a substantial relationship exists between arm muscle strength and eye coordination on shooting accuracy. Keywords: Arm muscle strength and hand-eye coordination, Shooting accuracy